2023
DOI: 10.1371/journal.pone.0283359
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance, Extended-Spectrum β-Lactamase production and virulence genes in Salmonella enterica and Escherichia coli isolates from estuarine environment

Abstract: The impact of antimicrobial resistance (AMR) on global public health has been widely documented. AMR in the environment poses a serious threat to both human and animal health but is frequently overlooked. This study aimed to characterize the association between phenotype and genotype of AMR, virulence genes and Extended-Spectrum β-Lactamase (ESBL) production from estuarine environment. The Salmonella (n = 126) and E. coli (n = 409) were isolated from oysters and estuarine water in Thailand. The isolates of Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The absence of the invA gene in Salmonella isolates may indicate non-invasiveness or the presence of alternative invasion mechanisms. 35 SPI-2 was associated with systemic infection and intracellular accumulation of Salmonella . It had 7 core effectors SseF, SseG, PipB, SteA, SifA, SteD and PipB2, which existed in all serotypes and could exert virulence effects on all hosts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The absence of the invA gene in Salmonella isolates may indicate non-invasiveness or the presence of alternative invasion mechanisms. 35 SPI-2 was associated with systemic infection and intracellular accumulation of Salmonella . It had 7 core effectors SseF, SseG, PipB, SteA, SifA, SteD and PipB2, which existed in all serotypes and could exert virulence effects on all hosts.…”
Section: Discussionmentioning
confidence: 98%
“… 34 Jeamsripong et al analyzed aquatic animals and estuarine environments, and found that Salmonella had the highest resistance to sulfamethoxazole at 95.2%, followed by trimethoprim (37.3%) and ampicillin (36.5%). 35 …”
Section: Discussionmentioning
confidence: 99%
“…S. typhimurium is spread by infected meat, eggs, and dung, among other things (Asefa Kebede and Duga 2022;Igbinosa et al 2023). When applied to croplands via animal manure, this bacterium, particularly those with antibiotic resistance, poses a major environmental and human health hazard that should be monitored closely (Jeamsripong et al 2023;Malik et al 2021). Australia's study showed contamination of 100% of broiler litter samples with Salmonella when reused as Organic Fertilizer on land (Kyakuwaire et al 2019).…”
Section: Salmonella Sppmentioning
confidence: 99%
“…Research on the river Rhine assessed AMR and virulence more directly, but was unable to establish any relationship, likely due to low measured prevalence of virulence genes [17]. A study of AMR and virulence in E. coli isolated from oysters and estuarine waters in Thailand found negative associations between sulfamethoxazole resistance and the toxin genes lt and stx [18]. Research on E. coli in spring water in the Eastern Indian Himalayas found a positive association between tetracycline resistance and the elt toxin gene and between quinolone resistance and the eae adhesin gene, along with a negative association between streptomycin resistance and two toxin genes [19].…”
Section: Introductionmentioning
confidence: 99%